Peran Mandor dalam Rekrutmen Pekerja Kontrak di Perkebunan Kelapa Sawit - Muhammad Said; Rina Hermawati; Junardi Harahap (Universitas Padjadjaran, 2023)
This study aims to describe the role of mandor (foreman) in recruiting contract workers at the oil palm plantation of PT. Bumi Pratama Khatulistiwa (BPK). They have a strategic role in the recruitment process so their presence is very important. For residents living surrounding the plantation, their opportunity to work in the company lies in the hands of the foreman. This research applied a descriptive analytic qualitative method. Informants for this research are foremen, contract workers, and local community leaders at PT. Bumi Pratama Khatulistiwa. The data were collected through observations and interviews. The study found that (1) palm oil plantations, especially PT. Bumi Pratama Khatulistiwa, has opened up quite broad opportunities for employment opportunities and has become a solution to economic problems for residents living surrounding the plantation; (2) foremen have power in recruiting workers through their access and network to workers; (3) contract workers or casual workers need cultural, social, economic and social capital, as well as symbolic capital with foremans and use each of those different capital in order to get a job in the palm oil plantation. The social capital and symbolic access at PT. BPK are the most influential factors in recruitment by foremen.